Comprehensive Analysis of Challenges and Opportunities for Chemistry Education Students: A Case Study of the 2024 Cohort - Pasaribu, Elida; Harahap, Iza; Marbun, Nova Fajria; Ravisa; Lumbangaol, Rosa; Daulay, Rabiah Afifah (Aspirasi Masyarakat Intelektual Islam Nusantara, 2024)
The rapid advancements in science and technology have transformed the educational landscape, presenting new challenges and opportunities for prospective educators. This study examines the demographic profile, technological gaps, and conceptual challenges faced by Chemistry Education students of the 2024 cohort at a higher education institution, especially in Universitas Negeri Medan. A mixed-methods approach was used, combining quantitative data analysis of 198 students with qualitative insights from surveys and interviews. Results indicate significant gender disparities, with female students forming the majority (26 Males and 172 Females), and highlight deficiencies in technological proficiency and conceptual understanding among students. The study concludes with actionable strategies, including targeted technological training, curriculum reform to incorporate project-based learning, and soft skills development, aimed at equipping students to excel as innovative and effective educators.